Application of Good Governance Principles in the Implementation of Regional Revenue and Expenditure Budget Management in South Konawe Regency - Hasrin; Nurdin (Papsel Journal of Humanities and Policy, 2024)
Good APBD management will have a positive impact on all levels of society, the hope of the Indonesian people. The problem formulation in this research is: 1. How can the principles of good governance be applied in administering the South Konawe Regency APBD? 2. What factors influence the implementation of South Konawe Regency APBD management? The objectives of this research are 1. To determine the application of good governance principles regarding transparency, legal compliance and accountability in regional financial management at the South Konawe Regency Regional Financial and Asset Management Service. 2. To find out the factors that influence the implementation of good governance in the management of the South Konawe Regency APBD. The advantages of this research are: 1. Conceptually, the results of this research are expected to improve and expand scientific understanding, especially in the study of financial management.2. In terms of implementation, it is hoped that the results of this research can provide input and suggestions to the South Konawe Regency Regional Financial and Asset Management Service so that transparency, compliance and accountability can be achieved in carrying out its functions and responsibilities.3. Methodologically, it can take the form of a study in the context of developing a research methodology that meets the practical and theoretical requirements of development administration studies. The research results show that the application of good governance principles in APBD management in South Konawe Regency has not met our expectations..